Management of thermally activated delayed fluorescence using a secondary electron accepting unit in thermally activated delayed fluorescent emitters. Issue 21 (14th May 2019) - Lee, Ha Lim; Lee, Kyung Hyung; Lee, Jun Yeob; Hong, Wan Pyo
Abstract : A molecular design approach adopting secondary electron accepting units in addition to a main electron acceptor was investigated as a strategy to manage the thermally activated delayed fluorescent (TADF) performance of the emitters. Abstract : A molecular design approach adopting secondary electron accepting units in addition to a main electron acceptor was investigated as a strategy to manage the thermally activated delayed fluorescent (TADF) performance of the emitters. A main skeleton possessing a benzofurocarbazole donor, a phenyl linker and a t -butylated diphenyltriazine acceptor was the platform of the molecular structures for high efficiency in TADF devices and CN units were attached to the phenyl linker as the secondary accepting unit. Either one or two CN units were introduced to examine the effect of the number of secondary electron accepting units on the TADF characteristics. Correlation of the number of secondary electron accepting units with the emission properties of the TADF emitters revealed that the introduction of one CN secondary electron accepting unit is ideal in terms of the TADF performance of the emitters. The TADF emitter without the CN secondary acceptor realized one of the highest efficiencies of 19.0% in deep blue TADF devices with a y color coordinate below 0.10 by introducing the t -butylated diphenyltriazine acceptor. Whereas, the TADF emitter with one CN secondary electron accepting unit displayed an even higher external quantum efficiency of 26.6%.